“A Legacy of Confusion”: An Exploratory Study of Service Provision under the Reinstated Interim Federal Health Program - Chen, Y.Y. Brandon; Gruben, Vanessa; Liew, Jamie Chai Yun (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2018)
Afer years of cuts, Canada’s refugee health-care program, the Interim Federal Health Program (IFHP), was fully restored in 2016. In this exploratory study, eleven semi-structured qualitative interviews were conducted with refugee service providers in the City of Ottawa to learn about their experience with the restored IFHP to date. Five themes emerged from the interviews: service provision challenges during the years of IFHP cuts; support for IFHP restoration; entitlement gaps in the current IFHP; ongoing confusion about the IFHP; and administrative barriers deterring health professionals from IFHP participation. More research is needed to determine whether the identifed challenges with the reinstated IFHP arise on a national scale.